Pandemic Leadership: Lessons from Bali Tourism Sector Approach to Covid-19 - Dodi Wirawan Irawanto; Pusvita Yuana; Khusnul Rofida Novianti; I Putu Satwika (APMBA (Asia Pacific Management and Business Application), 2021)
The current coronavirus outbreak is extraordinary within the toursim industry. It is the first pandemic of such magnitude to strike in modern toruism word when the world is more connected than at any previous moment in history. COVID-19 has generated unusual circumstances around the world, causing  tourism sector with “Business as Usual” to be disrupted, and everyone has accepted a new normal life using strict health protocol. The impact of the coronavirus (COVID-19) generated an economic and social shock, which will likely transform how people live and work, as well as how industries and organizations operate not to mention the tourism sector. This paper aims to analyze the leadership approach of the Indonesian government in the Bali tourism sector, which is the sector that produces the highest contribution to national income for Indonesia which has suffered the heaviest blow as a result of the Covid-19 pandemic.